Respostas
respondido por:
0
usando Bhaskara
Δ = b² - 4*a*c => Δ = (-2)² - 4*1*1 => Δ = 4 - 4 = > Δ = 0
-2 ± Raiz de Δ -2 ± raiz de 0 -2 ± 0
------------------ => ------------------ => --------
2 * a 2 * 1 2
![x' = \frac{2 + 0}{2} => x' = \frac{2}{2} => x' = 1 x' = \frac{2 + 0}{2} => x' = \frac{2}{2} => x' = 1](https://tex.z-dn.net/?f=x%27+%3D+%5Cfrac%7B2+%2B+0%7D%7B2%7D+%3D%26gt%3B+x%27+%3D+%5Cfrac%7B2%7D%7B2%7D+%3D%26gt%3B+x%27+%3D+1)
![x'' = \frac{2 - 0}{2} => x'' = \frac{2}{2} => x'' = 1 x'' = \frac{2 - 0}{2} => x'' = \frac{2}{2} => x'' = 1](https://tex.z-dn.net/?f=x%27%27+%3D+%5Cfrac%7B2+-+0%7D%7B2%7D+%3D%26gt%3B+x%27%27+%3D+%5Cfrac%7B2%7D%7B2%7D+%3D%26gt%3B+x%27%27+%3D+1)
Δ = b² - 4*a*c => Δ = (-2)² - 4*1*1 => Δ = 4 - 4 = > Δ = 0
-2 ± Raiz de Δ -2 ± raiz de 0 -2 ± 0
------------------ => ------------------ => --------
2 * a 2 * 1 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás